Brazil's New Era of Epidemics - Ian Read (Archives of Preventive Medicine - Peertechz Publications, 2020)
As 2020 nears an end, the Covid-19 pandemic has been deadlier in Brazil than in most other countries. The toll will likely cost 200,000 Brazilian lives before vaccines and other measures can turn the tide. The pandemic reveals a nation in the grip of a new era of epidemics. With anxious eyes we look ahead, but we should also look back.